1964
DOI: 10.4039/ent961450-11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Prespinning Eonymphs of the Swaine Jack-Pine Sawfly, Neodiprion swainei Midd. (Hymenoptera: Diprionidae)

Abstract: Laboratory experiments at various constant temperatures indicate a theoretical threshold of about 40°F. for spinning of cocoons by eonymphal larvae of Neodiprion swainei Midd. As temperatures fall below 52.5°F. the increase in mortality and time required to spin is pronounced. The optimum temperature is estimated to be around 60°F. Field investigations for three consecutive years show a close correlation between rate of spinning and temperature. Temperature is considered as a prime factor influencing the spinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Daylight surface temperatures are primarily determined by radiant energy (Maguire 1955 Larval drop occurs during the daylight hours as a rule so selection with respect to temperature is a likely possi-bility. Pilon, Tripp, McLeod, and Knitzky (1964) found that temperatures in the higher range (15.5 to 24?C) were most favorable for spinning of cocoons of N. swainei. Pilon, Tripp, McLeod, and Knitzky (1964) found that temperatures in the higher range (15.5 to 24?C) were most favorable for spinning of cocoons of N. swainei.…”
Section: Resultsmentioning
confidence: 93%
“…Daylight surface temperatures are primarily determined by radiant energy (Maguire 1955 Larval drop occurs during the daylight hours as a rule so selection with respect to temperature is a likely possi-bility. Pilon, Tripp, McLeod, and Knitzky (1964) found that temperatures in the higher range (15.5 to 24?C) were most favorable for spinning of cocoons of N. swainei. Pilon, Tripp, McLeod, and Knitzky (1964) found that temperatures in the higher range (15.5 to 24?C) were most favorable for spinning of cocoons of N. swainei.…”
Section: Resultsmentioning
confidence: 93%
“…When the eonymphs had spun cocoons, the latter were placed in numbered gelatin capsules and transferred to 4%-oz polyethylene Autopack containers (Pilon 1965) fitted over 16-oz glass jars containing a saturated salt solution to regulate relative humidity at 70-t-5 % . The cocoons were then kept at the same rearing conditions as the larvae.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the effects of temperature on the development of sawflies have been carried out for about 30 years (Gobeil 1941;Prebble 1941a, b, c; Brown and Daviault 1942;Elens 1953;Ohnesorge 1960;Wallace and Sullivan 1963;Pilon 1965;Pilon et al 1964;Sullivan 1965;Heron 1967;Sullivan and Wallace 1967). Papers dealing specifically with the Swaine jack-pine sawfly, Neodiprion swainei Midd., are those of Pilon et al (1964) and Pilon (1965), who respectively examined the influence of temperature on prespinning eonymphs and on adults.…”
Section: Introductionmentioning
confidence: 99%
“…Young larvae hatch in early August and feed as colonies on the previous year's foliage, during which they molt 4 to 7 times. Transformation to the ultimate instar, non-feeding stage, the p r e spinning eonymph, the stage attacked by E. amictorius and E. diprionis usually begins in late August or early September: The spinning period is variable (Tripp 1965;Pilon et al 1964), usually starting about the first of September, reaching a peak about midSeptember and ending in early October; although it has been known to peak as late as the first week in October and to last until late October or early November (Fig. 1 ) .…”
Section: Life Historiesmentioning
confidence: 99%